REKONSTRUKSI ISLAMISASI ILMU MODEL ISMAIL RAJI AL-FARUQI - Rizieq, Muhammad Faizal; Amril M; Yenni Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to examine and reconstruct the concept of Islamization of knowledge proposed by Ismail Raji Al-Faruqi in response to the dominance of Western epistemology in the modern academic world. This study employs a literature review method with a descriptive-analytical approach based on various relevant sources. The findings indicate that Al-Faruqi’s concept of Islamization of knowledge is grounded in the principle of tawhid, which emphasizes the unity of knowledge, unity of life, and unity of history, while rejecting the dichotomy between religious and secular sciences. The integration of naqli (revealed knowledge) and aqli (rational knowledge) becomes the core foundation in constructing a comprehensive Islamic scientific paradigm. However, the implementation of this concept faces significant challenges, particularly due to the strong influence of secular paradigms within modern educational systems. Furthermore, critiques from Ziauddin Sardar highlight that Islamization of knowledge should not merely involve adapting modern sciences, but must begin with the development of an independent Islamic epistemology. Therefore, a reconstruction of Al-Faruqi’s thought is necessary, directing it toward the development of an integrative, contextual Islamic science that is relevant to contemporary needs. This study concludes that the Islamization of knowledge is a strategic effort to rebuild Islamic civilization based on the values of tawhid, while remaining responsive to the dynamics of modern scientific development.